2014
DOI: 10.1002/anie.201402639
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity and Stability of Glucosinolates and Their Breakdown Products in Foods

Abstract: The chemistry of glucosinolates and their behavior during food processing is very complex. Their instability leads to the formation of a bunch of breakdown and reaction products that are very often reactive themselves. Although excessive consumption of cabbage varieties has been thought for long time to have adverse, especially goitrogenic effects, nowadays, epidemiologic studies provide data that there might be beneficial health effects as well. Especially Brassica vegetables, such as broccoli, radish, or cab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
180
0
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 266 publications
(196 citation statements)
references
References 302 publications
3
180
0
6
Order By: Relevance
“…Evidence for OCS emissions following SCN -degradation has been observed from a range of environmental samples from aquatic and terrestrial origins, indicating a wide distribution of OCS-emitting microorganisms in nature (Yamasaki et al, 2002). Hydrolysis of isothiocyanate, another breakdown product of 15 glucosinolates (Hanschen et al, 2014), by the SaxA protein also yields OCS, as shown in phytopathogenic Pectobacterium sp. (Welte et al, 2016).…”
Section: Other Terrestrial Ocs Flux Components 20mentioning
confidence: 90%
“…Evidence for OCS emissions following SCN -degradation has been observed from a range of environmental samples from aquatic and terrestrial origins, indicating a wide distribution of OCS-emitting microorganisms in nature (Yamasaki et al, 2002). Hydrolysis of isothiocyanate, another breakdown product of 15 glucosinolates (Hanschen et al, 2014), by the SaxA protein also yields OCS, as shown in phytopathogenic Pectobacterium sp. (Welte et al, 2016).…”
Section: Other Terrestrial Ocs Flux Components 20mentioning
confidence: 90%
“…Nonetheless, as most of vegetables that are abundant in 2-hydroxyalkenyl GLS are cooked before consumption, the goitrogenic action should not have been counted [39]. The study performed by Verkerk [40] showed the reduction (40-70%) in GLS content during cooking, which was mainly caused by the transition of these compounds to water.…”
Section: Comparison Of Different Cooking Methods (Traditional Cookingmentioning
confidence: 99%
“…The most common breakdown products are ITCs, which are characterised by odd mass of the molecular ion, and a [28] Beside identified ITCs, other breakdown products, mostly nitriles, can be helpful in confirming the parent GL identification. Individual GLs identified by GC-MS analysis of their hydrolysis products in different F. triquetra plant parts are shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%